Promoting Innovative Work Behavior: Investigating The Role of Islamic Work Ethic - Yayan Firmansah; Masyhuri Azhar; Md Atiqur Rahman Sarker; Ana Toni Roby Candra Yudha; Syahruddin Syahruddin (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
With respect to the global mission of Islamic higher education institutions for the Islamic world along with the highly volatile organizational environment and intense competition in the era of globalization, Islamic higher educations need to innovate. The existing literature reveals that innovation is one of the significant drivers for organizational competitive advantage. Innovation is very important for organizations to be able to survive in a dynamic and rapidly changing environment. However, existing studies have been silent regarding factors influencing administrative staff innovative behavior. This study then aims to analyze innovative work behavior of administrative staff and the factors that influence it, namely Islamic work ethics and organizational commitment. Quantitative approach was used. Sample was determined using purposive random sampling and data was collected by distributing questionnaires. The results of the analysis show that Islamic work ethic has no effect on innovative work behavior, while organizational commitment has a positive effect. However, these two variables have an effect on innovative work behavior simultaneously.